1998
DOI: 10.1016/s1097-2765(00)80165-3
|View full text |Cite
|
Sign up to set email alerts
|

The Histone H3–like TAF Is Broadly Required for Transcription in Yeast

Abstract: In yeast cells, independent depletion of TAFs (130, 67, 40, and 19) found specifically in TFIID results in selective effects on transcription, including a common effect on his3 core promoter function. In contrast, depletion of TAF17, which is also present in the SAGA histone acetylase complex, causes a decrease in transcription of most genes. However, TAF17-depleted cells maintain Ace1-dependent activation, and they induce de novo activation by heat shock factor in a manner predominantly associated with the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
115
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 53 publications
5
115
0
2
Order By: Relevance
“…Factors that preferentially repress T Cdirected transcription have also been identified (e.g., see Collart and Struhl 1994). In addition, some TAFs were found to be required for T C -dependent transcription but not T R -dependent transcription (Moqtaderi et al 1996(Moqtaderi et al , 1998. These findings, along with the observation that TAF dependence correlates with TAF occupancy at promoters (Kuras et al 2000;Li et al 2000), suggest that TFIID interacts with T C but not with T R .…”
Section: Tata 1 Versus Tatamentioning
confidence: 91%
“…Factors that preferentially repress T Cdirected transcription have also been identified (e.g., see Collart and Struhl 1994). In addition, some TAFs were found to be required for T C -dependent transcription but not T R -dependent transcription (Moqtaderi et al 1996(Moqtaderi et al , 1998. These findings, along with the observation that TAF dependence correlates with TAF occupancy at promoters (Kuras et al 2000;Li et al 2000), suggest that TFIID interacts with T C but not with T R .…”
Section: Tata 1 Versus Tatamentioning
confidence: 91%
“…Unexpectedly, initial studies revealed that the mutation or depletion of seven TAF II s individually resulted in gene-specific defects, and not global reductions in transcription Moqtaderi et al, 1996;Walker et al, 1996). In contrast, genetic analysis of other TFIID subunits that have sequence similarities to the core histones has shown that they are required for the transcription of a larger number of genes (Apone et al, 1998;Holstege et al, 1998;Michel et al, 1998;Moqtaderi et al, 1998;Natajaran et al, 1998;Sanders et al, 1999;Reese et al, 2000). The interpretation of these results is complicated by the presence of certain TAF II s in the SAGA histone acetyltransferase complex (Grant et al, 1998), and their function in multiple complexes may partially explain the expanded requirement for these TAF II s in transcription (Lee et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This core structure was suggested to depend upon the HFD, a structural motif shared by the core histones (22) and many other proteins (70). Nine of 14 yeast Tafps appear to contain HFDs, and subsets of these can form dimers with specific partner HFD Tafps (3,6,9,23,24,29,45,47,80). Indeed, Tan and colleagues (66) have described the formation and characterization of such an octameric complex comprised of four HFD-Tafps, a dimer of Taf6p-Taf9p bound to a dimer of Taf4p-Taf12p.…”
mentioning
confidence: 99%